2022
DOI: 10.1161/jaha.121.024091
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil‐to‐Lymphocyte Ratios in Patients Undergoing Aortic Valve Replacement: The PARTNER Trials and Registries

Abstract: Background The neutrophil‐to‐lymphocyte ratio (NLR) as a marker of systemic inflammation has been associated with worse prognosis in several chronic disease states, including heart failure. However, few data exist on the prognostic impact of elevated baseline NLR or change in NLR levels during follow‐up in patients undergoing transcatheter or surgical aortic valve replacement (TAVR or SAVR) for aortic stenosis. Methods and Results NLR was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Increased neutrophil‐to‐lymphocyte ratio (NLR) has been identified as a biomarker of systemic inflammation and CV disease. 7 , 8 , 9 , 10 NLR is derived from the absolute neutrophil count divided by the absolute lymphocyte count. Increased absolute neutrophil count is positively associated with adverse CV events, 9 , 11 , 12 , 13 , 14 , 15 whereas lymphocytes are suggested to be anti‐atherosclerotic and lymphocyte counts are lower in patients with vascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Increased neutrophil‐to‐lymphocyte ratio (NLR) has been identified as a biomarker of systemic inflammation and CV disease. 7 , 8 , 9 , 10 NLR is derived from the absolute neutrophil count divided by the absolute lymphocyte count. Increased absolute neutrophil count is positively associated with adverse CV events, 9 , 11 , 12 , 13 , 14 , 15 whereas lymphocytes are suggested to be anti‐atherosclerotic and lymphocyte counts are lower in patients with vascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Ozkan et al 19 Major observational studies and randomized controlled trials have identified some independent predictors of in-hospital and longterm mortality for patients with severe AS who underwent TAVR. 1,4,6,17,26 Previously, Lauridsen et al reported that among patients undergoing TAVR, an increasing risk of exacerbation with chronic obstructive pulmonary disease was associated with increasing 1-year mortality compared with non-chronic obstructive pulmonary disease patients. 27 Besides, left ventricular ejection fraction and advanced age as independent predictors of mortality are well…”
Section: Discussionmentioning
confidence: 99%
“…Although various etiological risk factors have been defined for degenerative AS, it is an inflammatory‐based disease that shares a common pathophysiology with atherosclerosis, including calcification, deposition of lipoproteins, and chronic inflammation 1 . Since AS is the result of not only aging but also a dynamic inflammatory process, it has been suggested that inflammatory biomarkers may predict outcomes in patients receiving TAVR 2–5 . Besides, malnutrition is one of the hallmarks of frailty in elderly patients and is a harbinger of worse outcomes in elderly patients with severe AS 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Recently, increased NLR was reported to be associated with malignant tumors, 11 inflammatory disease, 12 stoke, 13 and other diseases . In addition, both high neutrophil counts and lymphocytopenia were found to be associated with cardiovascular disease, 14,15 hence, neutrophil to lymphocyte ratio (NLR) has emerged as a new inflammation marker, which can better reflect the state of systematic inflammation.…”
Section: Introductionmentioning
confidence: 99%